2021
DOI: 10.3746/jkfn.2021.50.7.715
|View full text |Cite
|
Sign up to set email alerts
|

Quality Characteristics and Antioxidant Activity of Yanggaeng Added with Black Ginger (Kaempferia parviflora)

Abstract: The purpose of this study was to increase the availability and value of traditional foods by adding black ginger Yanggaeng. In this study, quality characteristics and antioxidant activity of Yanggaeng different (0%, 0.25%, 0.5%, 0.75%, and 1.0%) black ginger were analyzed. Yanggaeng's pH and sweetness showed no significant change with the addition of black ginger. The moisture content of the Yanggaeng increased with the increasing addition of black ginger powder. The color value indicated a significant decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…Hardness significantly decreased in the CQ powder-added groups, specifically CQ4 and CQ6, with values of 1687.78 and 1634.30, respectively, compared with the CON group. This reduced hardness follows a similar trend observed in studies in which natural additives, including tomato powder [3], black ginger [11], and fermented garlic paste [45] in Yanggaeng, were incorporated. Cohesion of Yanggaeng significantly decreased in CQ6, with a value of 0.27, compared to CON.…”
Section: Texture Profile Analysis Of Yanggaengsupporting
confidence: 82%
See 1 more Smart Citation
“…Hardness significantly decreased in the CQ powder-added groups, specifically CQ4 and CQ6, with values of 1687.78 and 1634.30, respectively, compared with the CON group. This reduced hardness follows a similar trend observed in studies in which natural additives, including tomato powder [3], black ginger [11], and fermented garlic paste [45] in Yanggaeng, were incorporated. Cohesion of Yanggaeng significantly decreased in CQ6, with a value of 0.27, compared to CON.…”
Section: Texture Profile Analysis Of Yanggaengsupporting
confidence: 82%
“…Therefore, research on Yanggaeng production, which includes various natural ingredients with physiological benefits, has become more active. For example, studies have reported adding ingredients such as barley sprouts [10], black ginger [11], finger root powder [12], tomatoes [3], mugwort powder [13], aronia juice [1], Enteromorpha prolifera [14], Hallabong orange [15], green tea powder [16], and paprika [17] to enhance the nutrition density and physiological properties of Yanggaeng.…”
Section: Introductionmentioning
confidence: 99%